Students’ Response Toward Teman Ritma Application as Mathematical Learning Media - Ramadhan, Ardhika Fajar; Nuryadi, Nuryadi; Marhaeni, Nafida Hetty; Rachmawati, Anna (AlphaMath : Journal of Mathematics Education, 2022)
The education sector has a vital role in the advancement of science and technology. One of the technological advances in the education sector is the use of android-based learning media. This study aims to determine students’ response to the use of the Teman Ritma application as a mathematics learning media and the influence of student learning outcomes on student response rates. This research is a quantitative descriptive with research instruments used: an android application, namely Teman Ritma and student response questionnaires. The research sample consisted of 32 students of 7th grade of SMPN 5 Yogyakarta. The sample was divided into two groups. The first group, known as K-1, contains 15 students with good learning outcomes, and the second group, known as K-2, contains 17 students with poor learning outcomes. The results from both groups showed that the response rate of all aspects assessed was very satisfactory and easily operated. This means that students can run the application without difficulty, and students easily get information from the material and do the exercises presented. Based on the student's response, the Teman Ritma application is eligible and practical to use as mathematics learning media. Then from the results of statistical tests, the learning outcomes affect students’ response rate for the learning design aspect. Meanwhile, learning outcomes have no effect on student response rate for operational and visual communication aspects.